Effects of teenage motherwood while at secondary school in rural communities of the Capricorn District, Limpopo Province - Nobukhosi, Maphophi Nandi (University of Limpopo, 2014)
The purpose of this study was to explore effects of teenage motherhood on the secondary education of the female learner. A qualitative research method and a descriptive, exploratory research design were adopted to undertake the study. Five one-on-one interviews were conducted and the data was analysed by using Tesch’s method of analysis. Three themes and nine sub-themes were generated from the analysed data. The research findings indicate that teenage motherhood does not have a negative effect on the ability of the learner to continue attending school, but also suggest that the various challenges experienced by the learner do have adverse effects on her school performance and ultimate decision to suspend school. There were other factors that influenced her academic performance and decision to continue or suspend school attendance; namely family support, experiences at school, as well as the cultural beliefs, traditions, and perceptions of the society she was living in. Key concepts: Teenage motherhood, effects, secondary education.
Thesis (M.Cur.) -- University of Limpopo, 2014
Keywords: Teenage mothers; Secondary schools; Rural communities; Limpopo Province; Effects; Teenage mothers -- South Africa -- Limpopo Province; Teenage mothers -- Vocational education